1994
DOI: 10.2307/1591831
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometric Analysis of B Cell and T Cell Subpopulations in Specific-Pathogen-Free Chickens Infected with Infectious Bursal Disease Virus

Abstract: Lymphocytes obtained from the blood, spleen, and bursa of normal chickens and of chickens infected with infectious bursal disease virus (IBDV) were analyzed for phenotypic expression of CT4, CT8, and immunoglobulin cell surface markers. Single-cell suspensions were stained with monoclonal antibodies by an indirect immunofluorescent assay, and percent staining was quantitated by flow cytometry. Although an appreciable decline from control levels in the percentage of lymphocytes expressing IgM was detected in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(35 citation statements)
references
References 11 publications
2
33
0
Order By: Relevance
“…IBDV-infected chickens become deficient in the production of optimum levels of antibodies against diverse antigens (Giambrone et al, 1977;Rodenberg et al, 1994). Although T cells do not serve as targets for IBDV replication, cell-mediated immune responses of virus-exposed chickens are compromised.…”
Section: Introductionmentioning
confidence: 99%
“…IBDV-infected chickens become deficient in the production of optimum levels of antibodies against diverse antigens (Giambrone et al, 1977;Rodenberg et al, 1994). Although T cells do not serve as targets for IBDV replication, cell-mediated immune responses of virus-exposed chickens are compromised.…”
Section: Introductionmentioning
confidence: 99%
“…It has been noted that the relative proportions of the CD4 and CD8 cells did not change in the BF after infection with cvIBDV (Rodenberg et al, 1994), although converse to these results, Williams and Davison (2005) found that CD4 and CD8 cells were obvious at 3 and 5 dpi respectively and remained at higher levels until 14 days. The γδTCR+ Tcell population was not affected in the thymus and showed a slight increase (P< 0.05) only at 5 dpi in BF after vvIBDV (strain UK661) infection (Williams and Davison, 2005).…”
Section: Cd4 and Cd8 Cellsmentioning
confidence: 78%
“…Perforin and granzyme-A dependant cytotoxic pathways of the cytotoxic T cell are mainly involved in the clearance of the IBDV from the BF, due to higher expression of these proteins in the CD4 and CD8 and BF cells (Rauf et al, 2011b). CD4 and CD8 cells populations appeared to increase in the BF, decrease in the thymus (particularly in the cortex), and show an increasing trend for CD4 and decreasing CD8, which was observed in the spleen in vvIBDV infected chickens (Carballeda et al, 2014), although results from work by Rodenberg et al (1994) were contradictory. It is not clear whether these higher populations are due to cell migration from the tissues to the periphery or contractions of the resident cells (Rasoli et al, 2015).…”
Section: Cd4 and Cd8 Cellsmentioning
confidence: 94%
“…IBDV targets cells of the BF where the virus predominantly focuses on infecting actively proliferating and differentiating lymphocytes of the B-cell lineage of the chicken [25]. Reports have documented global genomic changes in methylation patterns, including the novel epigenetic mark 5hmC, during both hallmarks of vertebrate Figure 2 The distribution of 5hmC and 5mC relative to B-cell localisation within the embryonic bursa of Fabricius.…”
Section: Discussionmentioning
confidence: 99%
“…Avian B-cells are crucial for inducing antibody responses against viral pathogens; in response viruses that infect birds often target B-cells to avoid elimination [22,23]. One such pathogen of veterinary and economic significance is infectious bursal disease virus (IBDV) which infects and subsequently causes cell death of developing B-cells as part of a mechanism to avoid elimination from the host [23][24][25]. Chickens within a commercially produced flock can recover from IBDV infection but remain immunosuppressed due, in part, to a reduced B-cell capacity.…”
Section: Introductionmentioning
confidence: 99%